Alternative to animal experimentation in pharmacology teaching: Development and validation of an equivalent digital learning tool - Roland Lawson; Sophie Leymarie; Claire Nikitopoulos; Antoine Humeau; Hichem Bouchenaki; Jean‐Luc Duroux; Laurent Fourcade; Sandrine Karam; Nicolas Picard; Claire Demiot (Wiley, 2022)
Abstract Regarding animal experiments in pharmacology teaching, ethical considerations led us to examine an alternative approach to the use of living animals. This study aimed to assess whether digital tools could replace live animal experiments in terms of motivation and knowledge acquisition. The study was carried out with students enrolled in the 5th year of the industry/research stream at the Faculty of Pharmacy of the University of Limoges. The participants were randomly assigned to groups of traditional or digital teaching methods, with the common theme of the class being the effect of a diuretic agent (furosemide) in rats. The scenario and learning objectives were identical for the two groups. Before the class and after randomization, the acceptance of the digital educational material was assessed with a scale, which predicts the acceptability of users according to individual dimensions and social representations, followed by the assessment of the motivation by a situational motivation scale (SIMS) for both groups. After the class, the students' motivation was assessed by a questionnaire based on Deci and Ryan's self‐determination theory. In the end, the participants were evaluated for homogeneity, based on general knowledge of renal pharmacology, and for knowledge acquisition concerning specific knowledge related to this teaching session. This study revealed a good acceptance of the digital tool and a good motivation toward the digital method among all the students. It found the two teaching methods (digital and traditional) to be equivalent in terms of motivation and knowledge acquisition. In our study, digital pedagogical tools as an alternative to live animals did not affect students' motivation and knowledge acquisition.